A small-scale proteomic approach reveals a survival strategy, including a reduction in alkaloid biosynthesis, in Hyoscyamus albus roots subjected to iron deficiency - Khandakar, Jebunnahar; Haraguchi, Izumi; Yamaguchi, Kenichi; Kitamura, Yoshie (Frontiers in Plant Science, 2013)
Hyoscyamus albus is a well-known source of the tropane alkaloids, hyoscyamine and scopolamine, which are biosynthesized in the roots. To assess the major biochemical adaptations that occur in the roots of this plant in response to iron deficiency, we used a small-scale proteomic approach in which 100 mg of root tips were treated with and without Fe, respectively, for 5 days. Two-dimensional mini gels showed that 48 spots were differentially accumulated between the two conditions of Fe availability and a further 36 proteins were identified from these spots using MALDI-QIT-TOF mass spectrometry. The proteins that showed elevated levels in the roots lacking Fe were found to be associated variously with carbohydrate metabolism, cell differentiation, secondary metabolism and oxidative defense. Most of the proteins involved in carbohydrate metabolism were increased in abundance, but mitochondrial NAD-dependent malate dehydrogenase was decreased, possibly resulting in malate secretion. Otherwise, all the proteins showing diminished levels in the roots were identified as either Fe-containing or ATP-requiring. For example, a significant decrease was observed in the levels of hyoscyamine 6beta-hydroxylase (H6H), which requires Fe and is involved in the conversion of hyoscyamine to scopolamine. To investigate the effects of Fe deficiency on alkaloid biosynthesis, gene expression studies were undertaken both for H6H and for another Fe-dependent protein, Cyp80F1, which is involved in the final stage of hyoscyamine biosynthesis. In addition, tropane alkaloid contents were determined. Reduced gene expression was observed in the case of both of these proteins and was accompanied by a decrease in the content of both hyoscyamine and scopolamine. Finally, we have discussed energetic and Fe-conservation strategies that might be adopted by the roots of H. albus to maintain iron homeostasis under Fe-limiting conditions.